The Structure of Hepatitis C Virus Genotypes/Subtypes in Adult Patients with Chronic Hepatitis C in the Moscow Region - E. N. Kudryavtseva; I. M. Korabelnikova; P. O. Bogomolov; O. S. Kuzmina; V. M. Matsievich; N. V. Voronkova; D. V. Dubodelov; V. F. Lavrov; T. A. Semenenko; S. N. Kuzin (Эпидемиология и вакцинопрофилактика, 2016)
The structure of HCV genotypes/subtypes and dynamics of its changes in a cohort of adult patients with chronic hepatitis C (n = 17229) was studied during 2008-2015 in the Moscow region. The prevalence of subtypes 1b and 3A HCV, whose relative density have made 47.5% (95%CI 46.8 - 48.3%) and 39.4% (95% CI 38.7 - 40.2 per cent) respectively was revealed. The average proportion of subtype 1A HCV was 5.4% (95%CI of 5.1 - 5.8%) and genotype 2 - 7.2% (95% CI 6,8 - 7,6%). It was established that the dynamics of 1b subtype HCV relative density was characterized by a moderate decline rate of 1.3% per year, while the proportion of subtype 3A HCV increased (+2.9% per year). The differences in the ratio of subtypes 1b and 3A HCV were revealed when dividing the patients by gender. The subtype 1b HCV was more frequently identified in women during the observation period. In the cohort of male patients a shift of the leading HCV subtype was detected - since 2010, the 3A subtype HCV was identified with a higher frequency than subtype 1b HCV. It was shown that in patients under 30 years the proportion of subtype 3A HCV was higher than in the age group older than 30 years, regardless of gender.